Availability and Readability of Emergency Preparedness Materials for Deaf and Hard-of-Hearing and Older Adult Populations: Issues and Assessments - Neuhauser, Linda; Ivey, Susan L.; Huang, Debbie; Engelman, Alina; Tseng, Winston; Dahrouge, Donna; Gurung, Sidhanta; Kealey, Melissa (PloS one, 2013)
A major public health challenge is to communicate effectively with vulnerable populations about preparing for disasters and other health emergencies. People who are Deaf or Hard of Hearing (Deaf/HH) and older adults are particularly vulnerable during health emergencies and require communications that are accessible and understandable. Although health literacy studies indicate that the readability of health communication materials often exceeds people's literacy levels, we could find no research about the readability of emergency preparedness materials (EPM) intended for Deaf/HH and older adult populations. The objective of this study was to explore issues related to EPM for Deaf/HH and older adult populations, to assess the availability and readability of materials for these populations, and to recommend improvements. In two California counties, we interviewed staff at 14 community-based organizations (CBOs) serving Deaf/HH clients and 20 CBOs serving older adults selected from a stratified, random sample of 227 CBOs. We collected 40 EPM from 10 CBOs and 2 public health departments and 40 EPM from 14 local and national websites with EPM for the public. We used computerized assessments to test the U.S. grade reading levels of the 16 eligible CBO and health department EPM, and the 18 eligible website materials. Results showed that less than half of CBOs had EPM for their clients. All EPM intended for clients of Deaf/HH-serving CBOs tested above the recommended 4(th) grade reading level, and 91% of the materials intended for clients of older adult-serving CBOs scored above the recommended 6(th) grade level. EPM for these populations should be widely available through CBOs and public health departments, adhere to health literacy principles, and be accessible in alternative formats including American Sign Language. Developers should engage the intended users of EPM as co-designers and testers. This study adds to the limited literature about EPM for these populations.